Sin City treachery - Gerlacher, Gary (Texas Black Rose Writing, 2024)
"Las Vegas, the entertainment capital of the world, hosts an F1 race, the largest sporting event in the city's history and a prime target for terrorism. With over a half million people descending on the Strip for the event, a bomb detonated in a parking garage days before the race. In the emergency room, Doc fights to save the lives of a pregnant doctor and her premature baby injured in the blast, spurring him to risk his own life to find justice for the victims. He is joined by his girlfriend Lana, a smart, ambitious reporter, his friend and colleague, Rick, and his trained ex-police dog Banshee. Their investigation takes them from a seedy bar to iconic landmarks around Las Vegas and crescendos on the night of the race when chaos reigns in the city. As the sun rises, they reveal a deceptive scheme to close the case."--Publisher.
115228
Keywords: Docker, AJ -- (Fictitious character) -- Fiction; Emergency physicians -- Nevada -- Fiction; Watchdogs -- Fiction; Belgian malinois -- Fiction; Terrorism -- Prevention -- Fiction; Friendship -- Fiction; Man-woman relationships -- Fiction; Las Vegas (Nev.) -- Fiction; Medical fiction; Detective and mystery fiction; Thrillers (Fiction)